Management of Arrhythmias After Heart Transplant: Current State and Considerations for Future Research. (17th March 2021) - Joglar, Jose A.; Wan, Elaine Y.; Chung, Mina K.; Gutierrez, Alejandra; Slaughter, Mark S.; Bateson, Brian P.; Loguidice, Michael; Drazner, Mark; Kistler, Peter M.; Saour, Basil; Poole, Jeanne E.; Murtaza, Ghulam; et al.
Abstract : Orthotropic heart transplantation remains the most effective therapy for patients with end-stage heart failure, with a median survival of ≈13 years. Yet, a number of complications are observed after orthotropic heart transplantation, including atrial and ventricular arrhythmias. Several factors contribute to arrhythmias, such as autonomic denervation, effect of the surgical technique, acute and chronic rejection, and transplant vasculopathy among others. To minimize risk of future arrhythmias, the bicaval technique and minimizing ischemic time are current surgical standards. Sinus node dysfunction is the most common indication for early (within 30 days) pacemaker implantation, whereas atrioventricular block incidence increases as time from transplant increases. Atrial fibrillation can occur in the first few weeks following transplantation but is uncommon in the long term unless secondary to a precipitant such as acute rejection. The most common atrial arrhythmias are atrial flutters, which are mainly typical, but atypical circuits can be observed such as those that involve the remnant donor atrium in regions immediately adjacent to the atrioatrial anastomosis suture line. Choosing the appropriate pharmacological therapy requires careful consideration due to the potential interaction with immunosuppressive agents. Despite historical concerns, adenosine is effective and safe at reduced doses if administered under cardiac monitoring. Catheter ablation has emerged as an effective treatment strategy for symptomatic supraventricular tachycardias, including ablation of atypical flutter circuits. Cardiac allograft vasculopathy is an important risk factor for sudden cardiac death, yet the role of prophylactic implantable cardioverter-defibrillator implant for sudden death prevention is unclear. Current indications for implantable cardioverter-defibrillator implantation are as in the nontransplant population. A number of questions for future research are posed.